2021
DOI: 10.3390/polym13213851
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L-lactic acid) Reinforced with Hydroxyapatite and Tungsten Disulfide Nanotubes

Abstract: Poly(L-lactic acid) (PLLA) is a biocompatible, biodegradable, and semi-crystalline polymer with numerous applications including food packaging, medical implants, stents, tissue engineering scaffolds, etc. Hydroxyapatite (HA) is the major component of natural bone. Conceptually, combining PLLA and HA could produce a bioceramic suitable for implants and bone repair. However, this nanocomposite suffers from poor mechanical behavior under tensile strain. In this study, films of PLLA and HA were prepared with small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…PTFE has excellent lubricity and corrosion resistance and can be used as the lubricating phase to reduce the wear of the coatings [ 31 , 32 ]. WS 2 crystals have a special interlayer crystalline structure, and the layers are connected by van der Waals forces, which have excellent lubricating properties [ 33 , 34 ]. The Ce 2 O 3 particles can be used as a reinforcing phase for wear and corrosion resistance [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…PTFE has excellent lubricity and corrosion resistance and can be used as the lubricating phase to reduce the wear of the coatings [ 31 , 32 ]. WS 2 crystals have a special interlayer crystalline structure, and the layers are connected by van der Waals forces, which have excellent lubricating properties [ 33 , 34 ]. The Ce 2 O 3 particles can be used as a reinforcing phase for wear and corrosion resistance [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…These results confirm that the addition of NC and nHA particles to the PLA matrix can improve the hardness of this polymer. A study by Golan et al [86] on the reinforcement of PLA with nHA and tungsten disulphide nanotubes showed that the HV of the PLA-nHA nanocomposite was higher than that of the neat PLA film by 1.4 times. Therefore, it was concluded that adding nHA particles to the PLA film increased the HV of the polymer.…”
Section: Hardnessmentioning
confidence: 99%
“…39 and 40. These nanotubes exhibited varying lengths (1-20 μm) and diameters (30-150 nm), as determined by careful analysis. 18 Notably, Fig. S1 † provides high-resolution scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images, offering visualization of the WS 2 nanotubes employed in this study.…”
Section: Synthesis and Characterization Of The Nanocomposite Fibersmentioning
confidence: 99%
“…Although the tungsten sulfur bond is six times weaker than the carbon-carbon bond, these nanomaterials present several unique advantages, as demonstrated before. [18][19][20] WS 2 INTs interact mostly via van der Waals forces, which are appreciably weaker than the π-π staking typical for aromatic systems like carbon nanotubes and graphene. Hence, in general WS 2 nanotubes disperse well and evenly in polymer matrices.…”
Section: Introductionmentioning
confidence: 99%